Phytoremediation of aquaculture effluents through the use of six marine microalgae: sustainability contributions in the sea urchin aquaculture industry in Argentina - Martelli, Antonela; Vanina Zualet, Tania; Miras Gagliardi, Maria Belén; Rubilar, Tamara (Revista de Biología Tropical, 2024)
Introduction: The aquaculture industry is constantly growing, registering a global production of almost 88 million tonnes by 2020. This industry brings environmental problems if its effluents are not properly treated. In 2020, the first technology-based company of CONICET was established in Argentine Patagonia whose purpose is the aquaculture production of the green sea urchin, Arbacia dufresnii to develop a range of nutraceutical products. Its cultivation system entails a commitment to sustainability since its creation, and yet it generates effluents with high levels of nitrates and phosphates. Objective: Given this scenario, and valuing bioremediation as a water treatment tool, the use of marine microalgae as phytoremediating agents of aquaculture effluent is proposed in this work. Methods: The microalgae Chaetoceros gracilis, Navicula sp., Tetraselmis suecica, Rhodomona salina, Nanochloropsis galvana and Cylindrotheca closterium were use; which are used as food for sea urchins larvae in the production process. An experiment was designed that compares the microalgal growth and the removal capacity of nutrients in the effluent in contrast to the artificial culture medium currently used in the production cycle. Results: It is possible to remedy the aquaculture industry’s effluent by employing the selected microalgae, with a percentage of removal efficiency of 100 % of the nitrate and an average removal efficiency percentage of 50 % for all the microalgae tested. Likewise, significantly higher microalgal biomass values were obtained when the culture was carried out in the effluent the culture in the artificial environment. Conclusions: The advances in research provided in this work show that it is possible to take advantage of a discard to cultivate microalgae, even improving microalgal productivity for use as food, reducing the costs involved in the microalgal production sector by changing the use of the type of current culture medium (F/2) for that from a current discard. These advances, if scaled and validated, can improve industry sustainability standards within the framework of a circular economy.